Case Report: Diagnosis and Therapy Technique for Dirofilariasis – Ehrlichiosis Coinfection in a Domestic Dog - Joan Elviyanti; Arief Purwo Mihardi; Anita Esfandiari; Rizal Arifin Akbari (Jurnal Sain Veteriner, 2023)
Multiple pathogenic agents, such as dirofilariasis and ehrlichiosis coinfection in the dog, cause coinfection disease. This paper aims to elucidate the diagnosis and therapy technique of dirofilariasis and ehrlichiosis coinfection disease in a dog. The owner brought a 4-year-old female dog named Lua to Rvet Clinic Tajur Halang Bogor with complaints of always painting when doing activities and lying down. The dog was just adopted one month from the shelter with many ticks and mosquitoes in the cage. The dog was diagnosed with dirofilariasis and ehrlichiosis by physical examination and laboratory tests. The laboratory tests included radiography, haematology, blood smear, and antigen test by SNAP® 4Dx® Plus Test (IDEXX, US). The dog was given doxycycline 10 mg/kg BW BID orally for three weeks, vitamin B12 0.025mg/kg BW BID orally for three weeks, furosemide 2 mg/kg BW SID orally for one week, Coenzyme-Q10 SID orally for three weeks, and selamectin topical drop every month for three months. A blood smear on the 21st day after therapy did not show microfilariae in 20 hpf with three repetitions. It means the therapy combinations are used effectively to reduce microfilariae and maintain the clinical sign of a dog due to dirofilariasis accompanied by ehrlichiosis.